Bandwidth and Gain Enhancement of MIMO Antenna by Using Ring and Circular Parasitic with Air-Gap Microstrip Structure - Teguh Firmansyah; Herudin Herudin; Suhendar Suhendar; Romi Wiryadinata; M Iman Santoso; Yus Rama Denny; Toto Supriyanto (Universitas Ahmad Dahlan, 2017)
This research was proposed a circular patch MIMO antenna by using a ring and circular parasitic radiator structure. As a novelty, in order to enhance bandwidth and gain of circular patch MIMO antenna, a conventional circular patch MIMO antenna will be added a ring and a circular parasitic. Therefore, this research was investigated a conventional MIMO antenna (C-MA), ring parasitic MIMO antenna (RP-MA), and circular parasitic MIMO antenna (CP-MA) as Model 1, Model 2, and Model 3, respectively. This MIMO antenna was designed on FR4 microstrip substrate with r= 4.4, thickness h=1.6 mm, and tan = 0.0265. This MIMO antenna has center frequency 2.35 GHz which is a frequency band for LTE application in Indonesia. An Advance Design System (ADS) software was used to determine the antenna parameters. The MIMO antenna C-MA / RP-MA/ CP-MA achieves 2.36GHz/ 2.38GHz/ 2.38 GHz, 70 MHz/ 100 MHz/ 120 MHz, 1.625 dBi/ 4.066 dBi/ 4.117 dBi, 6.414 dBi/ 7.26 dBi/ 7.153 dBi, 33.9 %/ 47.8 %/ 49.70 %, -12.35 dB/ -22.21 dB/ -23.66 dB, and -30.924 dB/ -28.46 dB/ -27.59 dB for center frequency, bandwidth, gain, directivity, efficiency, reflection coefficient, and mutual coupling, respectively. Compared to C-MA (Model1) performances, The result showed that proposed antenna has wider-bandwidth/ higher-gain with 42.8%/ 150.2 %, and 71.4%/ 163.3% for RP-MA (Model 2) and CP-MA (Model 3), respectively. The proposed antenna has size of 50 mm x 130 mm x 23.2 mm. Measured results are in a good agreement with the simulated results.